Two worlds. An imaginary speech delivered before judge Webster Thayen. Why sentence of death should not be pronounced on him and Nicola Sacco. [Ed.] by M.A. Cohn. [Forew. by L.D. Abbott] (New York, 1927)
Publ. by Independent Sacco-Vanzetti committee.